No Association Between MicroRNA-608 rs4919510 G>C Polymorphism and Digestive System Cancers Susceptibility: A Meta-Analysis Based on 10,836 Individuals - Li, Xue-Feng; Song, Ju-Kun; Cai, Jun-Wei; Zeng, Yu-Qin; Li, Min; Zhu, Jie; Niu, Yu-Ming (Frontiers in Physiology, 2018)
Previous epidemiologic studies have revealed a possible association between microRNA-608 rs4919510 G>C polymorphism and digestive system cancers (DSCs) risk, but the results were not consistent. We therefore performed an updated meta-analysis to explore the association between microRNA-608 rs4919510 G>C polymorphism and DSCs risk. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to assess the relationship between the microRNA-608 rs4919510 G>C polymorphism and DSCs risk. Heterogeneity, cumulative analyses, sensitivity analyses, and publication bias were also conducted to examine the statistical power. Eight published articles with nine independent case-control studies involving 10,836 individuals were included in this meta-analysis. Overall, no significant association was found between microRNA-608 rs4919510 G>C polymorphism and DSCs risk in general populations. But some significant protective effects were observed in the subgroup of Caucasian population group in three genetic models (C vs. G: OR = 0.82, 95% CI, 0.68–0.99, P = 0.03, I2 = 0%; CC vs. GG: OR = 0.59, 95% CI = 0.36–0.97, P = 0.04, I2 = 0%; GC+CC vs. GG: OR = 0.61, 95% CI = 0.37–0.99, P = 0.05, I2 = 0%). In summary, current evidence indicates that the microRNA-608 rs4919510 G>C polymorphism maybe an important factor of DSCs susceptibility, especially in Caucasian population.